(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
In this article, the work on the introduction of the Uzbek language as a state language and the increase of the position of the Uzbek language among world languages, as well as the practical results of these reforms are explained scientifically.